2016
DOI: 10.1097/pas.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Study of Pediatric Spindle and Sclerosing Rhabdomyosarcoma

Abstract: Sclerosing and spindle cell rhabdomyosarcoma (SRMS) have been recently re-classified as a stand-alone pathologic entity, separate from embryonal RMS (ERMS). Genetically a subset of the congenital cases display NCOA2 gene rearrangements, while tumors occurring in older children or adults harbor MYOD1 gene mutations with or without coexisting PIK3CA mutations. Despite these recent advances, a significant number of tumors lack known genetic alterations. In this study we sought to investigate a large group of pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 228 publications
(131 citation statements)
references
References 42 publications
(55 reference statements)
3
127
0
1
Order By: Relevance
“…In contrast to the spindle cell sarcomas that frequently occur in this age group, such as ETV6-NTRK3 fusion-positive infantile fibrosarcoma 20 and less commonly congenital spindle cell rhabdomyosarcoma with VGLL2 -related fusions, 21 most of the well-established round cell sarcoma entities, such as Ewing sarcoma, desmoplastic round cell sarcoma, or sarcomas with CIC-DUX4 or BCOR - CCNB3 fusions rarely occur in infants. 16,2228 In fact, in our database of 31 infantile round cell sarcomas occurring in soft tissue, only 2 (6.5%) cases had known gene fusions (one EWSR1-ERG , the other EWSR1-ETV4) .…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to the spindle cell sarcomas that frequently occur in this age group, such as ETV6-NTRK3 fusion-positive infantile fibrosarcoma 20 and less commonly congenital spindle cell rhabdomyosarcoma with VGLL2 -related fusions, 21 most of the well-established round cell sarcoma entities, such as Ewing sarcoma, desmoplastic round cell sarcoma, or sarcomas with CIC-DUX4 or BCOR - CCNB3 fusions rarely occur in infants. 16,2228 In fact, in our database of 31 infantile round cell sarcomas occurring in soft tissue, only 2 (6.5%) cases had known gene fusions (one EWSR1-ERG , the other EWSR1-ETV4) .…”
Section: Discussionmentioning
confidence: 92%
“…The spindle cell variant was included within the embryonal category along with botryoid and anaplastic variants. Recent evidence, however, suggests that the spindle cell and sclerosing RMS may represent a discrete morphologic spectrum from the embryonal subtype because of similar clinical presentations and histologic features [7]. Specifically, there is a subtype of spindle cell variant which displays areas of prominent hyaline sclerosis and a pseudovascular growth pattern, overlapping with the morphology of sclerosing RMS.…”
Section: Discussionmentioning
confidence: 99%
“…Other genetic alterations include the NCOA2 gene fusion, which is common in congenital cases, and the MYOD1 gene mutation, which tends to occur in older children and adults. They found that cases which harbor gene fusions involving VGLL2 and NCOA2 had a favorable clinical outcome, whereas tumors associated with mutations in the MYOD1 gene showed a more aggressive course with a higher mortality despite multimodal therapy [7]. …”
Section: Discussionmentioning
confidence: 99%
“…ScRMS may show in addition an undifferentiated round cell component arranged in a pseudovascular or pseudoalveolar pattern in a prominent hyalinized stroma [19, 20]. SRMS-ScRMS share genetic alterations, although these vary depending on the clinical presentation: recurrent NCOA2 and VGLL2 related fusions in congenital/infantile setting, which are associated with a favorable outcome [21, 22], or MYOD1 -mutations in older children and adults are associated with a poor prognosis [23-26], Pleomorphic RMS is a rare variant, usually diagnosed in patients over the age of 45 years, with a morphologic appearance of large pleomorphic cells [9, 27]. …”
Section: Introductionmentioning
confidence: 99%